Effects of nutrition education on adipocytokines levels in cord blood at birth - Yıldızlı, Feride; Bulduk, Emre Özgür; Bulduk, Sıdıka; Coşkun, Burcu Biral (Progress in Nutrition, 2018)
Background/aims: Adipocytokines play a role in intrauterine growth but the effects of the nutrition education on adipocytokines and physical measurements at birth remains unclear. The aim of this study was to evaluate effects of nutrition education on adipocytokines levels in cord blood and physical measurements at birth. Methods: The present study involved 52 pregnant women who were in pregnancy followed up in Gazi University Medical School Hospital at Ankara, Turkey. They were randomly divided into two groups and experimental group involved in nutrition education. Results: There was a positive association between the cord blood leptin values of the both groups. Nutrition education had no significant effect on cord blood adiponectin, visfatin and IL-6 values of the newborns. Also there was not a significant difference between the average values of weight and the head circumference of newborns in both groups. In experimental group, the average birth length was observed to be higher than that of control group. Conclusion: Nutrition education might improve leptin levels of the newborns in the experimental group. In the lights of these results, it may be suggested that higher cord blood leptin levels could play an important role in higher birth length values of the newborns.